SmoothRide: A Versatile Solution to Combat Cybersickness in Elevation-Altering Environments - Ang, Samuel; Quarles, John (IEEE transactions on visualization and computer graphics, 2024)
Cybersickness continues to bar many individuals from taking full advantage of virtual reality (VR) technology. Previous work has established that navigating virtual terrain with elevation changes poses a significant risk in this regard. In this paper, we investigate the effectiveness of three cybersickness reduction strategies on users performing a navigation task across virtual elevation-altering terrain. These strategies include static field of view (FOV) reduction, a flat surface approach that disables terrain collision and maintains constant elevation for users, and SmoothRide, a novel technique designed to dampen a user's perception of vertical motion as they travel. To assess the impact of these strategies, we conducted a within-subjects study involving 61 participants. Each strategy was compared against a control condition, where users navigated across terrain without any cybersickness reduction measures in place. Cybersickness data were collected using the Fast Motion Sickness Scale (FMS) and Simulator Sickness Questionnaire (SSQ), along with galvanic skin response (GSR) data. We measured user presence using the IGroup Presence questionnaire (IPQ) and a Single-Item Presence Scale (SIP). Our findings reveal that users experienced significantly lower levels of cybersickness using SmoothRide or FOV reduction. Presence scores reported on the IPQ were statistically similar between SmoothRide and the control condition. Conversely, terrain flattening had adverse effects on user presence scores, and we could not identify a significant effect on cybersickness compared to the control. We demonstrate that SmoothRide is an effective, lightweight, configurable, and easy-to-integrate tool for reducing cybersickness in simulations featuring elevation-altering terrain.